2012
DOI: 10.1002/bip.22165
|View full text |Cite
|
Sign up to set email alerts
|

Fine mapping of a monoclonal antibody to the N‐Methyl D‐aspartate receptor reveals a short linear epitope

Abstract: Anti-N-Methyl D-aspartate receptor encephalitis is an autoimmune disease in which autoantibodies are produced against extracellular regions of the N-Methyl D-aspartate receptor (NMDAR). In this study, we used resin-bound peptides equipped with a base labile linker to map the epitope of a monoclonal NMDAR antibody against the NMDAR NR1 subunit. The antigenicity of the synthesized resin-bound peptides was determined by enzyme-linked immunosorbent assay. Distinct reactivity was found to two extracellular overlapp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 32 publications
11
26
0
Order By: Relevance
“…As seen, the two epitopes were located in flexible structures, although the N ‐terminal end of the mAb SSI‐HYB 358‐02 epitope was found to be located in an α‐helical structure. These findings are in accordance to the literature, describing that epitopes often are located in flexible structures, although the Ro60 protein is rich in ordered structures, such as α‐helices. Thorough analysis of the Ro60 epitopes identified the aa sequences MQPLNEKQIA and RFLCFGSEGGTYYIK as the epitopes of mAbs TROVE2 and SSI‐HYB 358‐02, respectively.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…As seen, the two epitopes were located in flexible structures, although the N ‐terminal end of the mAb SSI‐HYB 358‐02 epitope was found to be located in an α‐helical structure. These findings are in accordance to the literature, describing that epitopes often are located in flexible structures, although the Ro60 protein is rich in ordered structures, such as α‐helices. Thorough analysis of the Ro60 epitopes identified the aa sequences MQPLNEKQIA and RFLCFGSEGGTYYIK as the epitopes of mAbs TROVE2 and SSI‐HYB 358‐02, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…Especially, the specific side‐chains of Glu and the two Tyr residues were found to be crucial for antibody reactivity. These findings are in accordance with the literature, describing that charged and hydrophilic aas are often essential for Ab reactivity . Charged aas like Lys, Arg and Glu and hydrophilic aas like Asn and Thr are typical aas in B‐cell epitopes, due to their capability to form a multitude of stable interactions …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Protease substrates γ-secretase TM peptide substrates/AD [41] Protease inhibitors HIV-protease inhibitors/HIV subtype C [42] Cell adhesion N-methylated TSP-1 peptides/CLL [43] Peptide antibody production P110/ mycoplasma genitalium, b-raf/ malignant melanoma [44,45] Epitope identification GAD/ diabetes, CENPF/ cancer, NMDAR/ encephalitis [34,46,47…”
Section: Researchmentioning
confidence: 99%
“…In anti-NMDAR encephalitis, anti-neural antibodies cause selective and reversible capping and internalization of surface NMDARs in the brain, leading to severe dysfunction of neocortical memory, learning, and cognitive abilities Dalmau et al 2011); however, it remains controversial which subunit is more important in the pathogenesis of anti-NMDAR encephalitis. Gleichman et al (2012) and Amrutkar et al (2012) emphasized that a small region (N386/G369) within an extracellular N-terminal domain of the NR1 subunit was crucial for the development of immunoreactivity and the subsequent dysfunction of NMDARs. Mikasova et al (2012) reported that anti-NMDAR antibodies produced differential effects on the two main NR2A-and NR2B-containing subtypes.…”
Section: Discussionmentioning
confidence: 99%